Review the Readiness of MSMEs in Indonesia Compliance with Accounting Standards Micro, Small and Medium Enterprise (SAK EMKM) - Samsiah, Siti; Lawita, Nadia Fathurrahmi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2017)
This research demonstrates that despite being late to have financial reporting standards for Micro, small and medium enterprises which could help MSMEs in Indonesia in funding and for tax purposes, the willingness and readiness of the business are still questionable. This paper will first discuss a new accounting standard ruled by The Indonesian Institute of Accountants (IAI) for micro, small and medium enterprise (MSMEs) (SAK EMKM) that was adopted from IFRS and then discuss the readiness of the business to implement it. This research uses the qualitative approach with the method of in-depth interviews. From the results of interviews with several business actors, some major issues were found, such as, in general, SMEs do not make a financial record of business, the cause is the lack of human resources owned SMEs to prepare financial statements.